PENGARUH POLA ASUH ORANG TUA TERHADAP PERILAKU ANAK DI ERA TEKNOLOGI 5.0 : STUDI KASUS DI KAMPUNG TAMANSARI DESA MURUY KECAMATAN MENES KABUPATEN PANDEGLANG - Rahmatullah, Muhammad Asep; Mas'ud, muhamad; Rahmawati, Aslihatul (Program Studi Pendidikan Agama Islam Program Pascasarjana Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2023)
The reality of children's moral behavior in Tamansari Village, Muruy Village, Menes Pandeglang District is currently very worrying due to the negative impacts of using technology 5.0. The first education children receive is parental education at home, namely the parenting style of parents towards children. Parenting patterns to implement Islamic education to protect children's behavior from the negative impacts of technology 5.0. This research method uses a qualitative approach with case study research. The techniques used in collecting data are observation, interviews and documentation techniques. Meanwhile, the data analysis technique used is the Milles Hiberman technique through data reduction, data presentation, and drawing conclusions from the research. The results of this research are (1) the influence of early childhood parenting patterns in the technology 5.0 era used by parents, namely indifferent, permissive and democratic. (2) The behavior of Tamansari Muruy village children tends to be impolite, unethical and often disobedient. And few children have good moral behavior. (3) Islamic education has an important role in helping parents in forming the moral character of children, so that civilized behavior, morals and good manners are formed.